Role of maternal factors, PAPP-A, and Doppler in screening for early- and late-onset pregnancy hypertension in Asian population. (2nd July 2016) - Kumar, Manisha; Sharma, Karuna; Singh, Ritu; Singh, Shalini; Ravi, V.; Singh, Kamlesh; Gupta, Usha; Bhattacharya, J.
ABSTRACT: Objective : To determine the predictive value of biochemical markers, uterine artery Doppler, and maternal factors in predicting early-onset (EO) and late-onset (LO) pregnancy hypertension. Methodology : All singleton pregnancies between 11 and 13 weeks and 6 days gestation underwent estimation of body mass index (BMI), mean arterial pressure (MAP), uterine artery Doppler pulsatality index (PI, and resistance index), biomarker PAPP-A, and free β-hCG. Women who developed hypertension were treated as cases and normotensives were taken as controls. The cases were further divided into EO and LO hypertension. The comparison was undertaken by appropriate statistical analysis. Results : Pregnancy hypertension was seen in 399 (13.2%) women. EO hypertension was seen in 153 (38.3%), whereas LO was observed in 246 (61.7%). The significant markers for predicting hypertension in pregnancy were maternal age, BMI, MAP, uterine artery Doppler PI, and PAPP-A. A combination of MAP and BMI was a better predictor (sensitivity and specificity 80% and 52%, respectively) than PAPP-A and Doppler combined (sensitivity and specificity 62% and 52%, respectively). When all the above markers were combined, the sensitivity and specificity of the test was 73% and 70%, respectively. EO hypertension was better predicted compared with LO. The negative predictive value (NPV) of the test was above 90%, suggesting that if a woman had the marker below the cutoff, there was more than 90% chance that she would not develop hypertension later in pregnancy. Conclusion : A combination of variables increased the sensitivity and specificity of the test for hypertension in pregnancy. The markers examined were a predictor of EO hypertension, with a high NPV, making it a good screening test.